An Empirical Profile of Future Work Self-Salience Among Senior High School Students in Makassar: Implications for Digital Career Guidance - Alfikriah Syahira; Muslihati; Zamroni (UIN Siber Syekh Nurjati Cirebon, 2026)
Technological advances, automation, and artificial intelligence have made the future of work increasingly dynamic and unpredictable, requiring students to develop career readiness beyond choosing a major, including the ability to envision and direct themselves toward a desired future work self. This urgency is salient in Indonesia given the persistently high unemployment rate among senior secondary and vocational graduates, while research on Future Work Self-Salience (FWSS), a salient representation of oneself in future work, has mostly focused on university students and employees rather than senior high school students, who are at a critical stage of career identity formation. This study aimed to describe the level of FWSS among eleventh-grade students in Makassar City, analyze gender differences, and outline its practical application for adaptive, contextual career guidance and counseling services. A quantitative cross-sectional survey was conducted with 160 students (80 male, 80 female) from 11 senior high schools, measured using the FWSS Scale and analyzed using descriptive statistics and the Mann-Whitney U test. Results showed that students FWSS generally fell into the moderate category (73.75%; M = 14.09; range 5-20), with work-identity clarity developing more strongly than job-type clarity, and a significant gender difference was found (U = 4024; p = .005; r_rb = .258), with male students scoring higher. The study concludes that senior high school students in Makassar City have begun forming a future work orientation but still require systematic, gender-sensitive support, positioning the FWSS profile as an empirical basis for developing needs-based, digitally oriented career guidance and counseling services.